2017
DOI: 10.20319/mijst.2017.31.91103
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metal Ions in Water Using Modified Polyamide Thin Film Composite Membranes

Abstract: Heavy metals in the wastewater

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Heavy metals can build up in soil environments and can transfer across the food chains, causing negative health impacts on human and animals. A number of studies have shown heavy metals as imperative environmental contaminants (Abbas et al 2010;Sobukola, Adeniran, Odedairo & Kajihausa, 2010;Kaur & Goyal, 2011;Asdeo & Loonker, 2011;Hu et al 2012;Kananke, Wansapala & Gunaratne, 2014, 2015Haneef &Akintug, 2016 andNgo &Tran, 2017). Through the atmospheric deposition or road runoff, metals are absorbed into the plant tissues of green leafy vegetables (GLV) which are cultivated and marketed along roadsides.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals can build up in soil environments and can transfer across the food chains, causing negative health impacts on human and animals. A number of studies have shown heavy metals as imperative environmental contaminants (Abbas et al 2010;Sobukola, Adeniran, Odedairo & Kajihausa, 2010;Kaur & Goyal, 2011;Asdeo & Loonker, 2011;Hu et al 2012;Kananke, Wansapala & Gunaratne, 2014, 2015Haneef &Akintug, 2016 andNgo &Tran, 2017). Through the atmospheric deposition or road runoff, metals are absorbed into the plant tissues of green leafy vegetables (GLV) which are cultivated and marketed along roadsides.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nearly 75% of the three million early deaths found in developing countries are water borne (Ali, 2012). For this reason the maintenance of public health through the treatment of water remains of high importance to policy makers around the world (Hong, 2017). As such the optimization of treatment processes as well as the ability to predict the water quality over time is a key part of decision-making processes in water treatment industries as it allows the provision of a sustainable supply of good quality water to the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Composite membranes have recently attracted attention as each layer can be independently modified to achieve the desired membrane characteristics (Hong Anh Ngo, & Thi Tran, 2017). In particular, ceramic membranes remain one of the most promising technologies among membrane processes due to their superior performance, hydrophilicity, mechanical robustness, and high thermal and chemical stabilities.…”
Section: Introductionmentioning
confidence: 99%